Anti-slip paper base for coating mold and preparation method of anti-slip paper base
By setting a double-sided coating layer on the anti-slip paper base coated with abrasives, using components such as styrene propane latex, styrene butadiene latex, and adding nanomaterials such as nanosilica and nanocalcium carbonate, the performance degradation of existing coated abrasives in humid environments and high temperature and high humidity conditions is solved, and excellent anti-slip effect and abrasive particle stability are achieved.
Patent Information
- Application Number
- CN202411996310.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-12-31
AI Technical Summary
The existing coated abrasives lack effective anti-slip design, resulting in a degradation in humid environments and high temperature and humidity conditions. Traditional binders are prone to failure when extreme temperature changes, affecting the stability of abrasive particles.
An anti-slip paper base for coating molds is adopted, and a coating layer is provided on the front and back of the substrate. The coating layer contains components such as styrene propylene latex, styrene butadiene latex, polyurethane resin, modified alkali lignin, nanosilica and nanocalcium carbonate. Through high-temperature cross-linking and the use of nanomaterials, a composite coated anti-slip paper with excellent anti-slip properties is formed.
It achieves excellent anti-slip effect in humid environments and high temperature and humidity conditions, extends the service life of coated abrasives, improves the safety and efficiency of operation, and enhances the stability and wear resistance of abrasive particles.
Smart Images

Figure BDA0005224581930000121
Abstract
Description
Technical Field
[0001] The present application belongs to the technical field of papermaking, and in particular relates to a non-slip paper base for coating molds and a preparation method thereof. Background Art
[0002] As a key industrial tool, coated abrasives are widely used in many fields such as automobile manufacturing, metal processing, furniture production and electronic equipment assembly. Its basic structure is to fix the abrasive on a flexible or semi-rigid substrate through a binder, providing efficient grinding and polishing services for various complex-shaped workpiece surfaces. With the continuous improvement of the processing accuracy requirements of modern manufacturing industry and the growing market demand for efficient, safe and environmentally friendly products, the research and development and application of coated abrasives have become an important focus of the industry.
[0003] The core of coated abrasives is their ability to flexibly adapt to different types of workpieces and maintain good performance during operation. This not only involves selecting the right substrate material to ensure sufficient mechanical strength and support, but also requires considering how to improve the product's wear resistance and tear resistance to extend its service life and reduce the frequency of replacement. In addition, when facing a humid environment, coated abrasives should have excellent water resistance to prevent structural damage or performance degradation due to water intrusion. At the same time, in order to ensure the safety of users and improve work efficiency, coated abrasives must have certain anti-slip properties to avoid accidental slipping during handheld operations.
[0004] Although the existing coated abrasive technology has reached a high level in some aspects, there are still many problems to be solved in practical applications. Traditional coated abrasives mostly use paper, cloth or synthetic fiber fabric as the substrate, and use natural rubber, animal glue or synthetic resin as the binder to fix the abrasive grains, but the existing technology still has some limitations.
[0005] Ordinary paper-based materials tend to lose hardness under wet conditions, affecting the grinding effect; while cloth or synthetic fiber fabrics may wear or tear under high-intensity use, resulting in a shortened product life. Traditional binders are prone to failure under extreme temperature changes or contact with liquids, which may cause abrasive particles to fall off, thereby reducing work efficiency. Especially in high temperature and high humidity environments, the performance stability of binders is an important challenge. In addition, existing coated abrasives lack effective anti-slip designs, which reduces the safety and efficiency of operations and increases safety hazards. The current manufacturing process still has room for improvement in achieving control accuracy and uniformity of abrasive distribution and coating thickness. There is also room for optimization in drying technology and surface modification methods. For example, the traditional drying process is time-consuming, affecting production efficiency; the surface modification technology is relatively single and it is difficult to form complex textures, which limits the aesthetics and anti-slip effect of the product.
[0006] In summary, although the current coated abrasive technology has achieved certain achievements, there are still many problems that need to be solved in practical applications. Summary of the invention
[0007] In order to solve the problem that coated abrasives in the prior art lack effective anti-slip design, the present application provides an anti-slip paper base for a coated mold and a preparation method thereof. The anti-slip paper base is provided with a coating layer on both the front and back sides of the base, achieving an excellent anti-slip effect.
[0008] The present application provides a non-slip paper base for a coating mold, which comprises the following structures in order: a front coating layer, a substrate and a back coating layer, wherein the front coating layer and the back coating layer are attached to both sides of the substrate;
[0009] The front coating layer comprises the following components by weight:
[0010] 30-60 parts of styrene-acrylic latex, 30-60 parts of styrene-butadiene latex, 10-20 parts of polyurethane resin, 3-7 parts of modified alkali lignin;
[0011] The substrate is a paper substrate;
[0012] The back coating layer comprises the following components by weight:
[0013] 30-60 parts of styrene-acrylic latex, 30-60 parts of styrene-butadiene latex, 1-2 parts of nano-silicon dioxide, 2-12 parts of nano-calcium carbonate, 1-2 parts of glycerol, 3-7 parts of modified alkali lignin, and 1-2 parts of drying agent.
[0014] The present application also provides a method for preparing a non-slip paper base for coating a mold, comprising the following steps:
[0015] S1. crushing coniferous and hardwood pulp at a crushing concentration of 5.0% to 4.0%, and beating the pulp with a refiner to a beating degree of 30 to 40° SR to obtain beaten wood pulp;
[0016] S2, putting defoamer, PAE wet strength agent, polyacrylamide and aluminum sulfate into the adding tank, pumping the wood pulp obtained in S1 into the adding tank in advance, and adjusting the concentration to 3% to 3.5%, performing internal sizing to obtain slurry;
[0017] S3, forming the slurry in step S2 through a fourdrinier paper machine, spraying starch on the wet end after forming, spraying starch and alkyl ketene dimer sizing agent on the front and back of the paper surface at the same time, and performing web-end glue spraying;
[0018] S4, after the web is sprayed with glue, it is pressed and then dried at a temperature of 90-130°C for 30-180s;
[0019] S5, after drying, add the glue applicator to carry out cadre dipping, and then dry again;
[0020] S6, after drying, calendering is performed using a calender to obtain a substrate;
[0021] S7, coating the front side of the calendered substrate, and then crosslinking at a high temperature of 130° C. to 150° C. for 30 to 120 seconds to obtain a front side coating layer;
[0022] S8, then back coating is performed, and then high temperature cross-linking is performed at 130° C. to 150° C. for 30 to 120 seconds to obtain a back coating layer;
[0023] S9, modifying the paper using a groove roller;
[0024] S10, using a winding device to roll up, and packaging to obtain the anti-slip coated paper base.
[0025] Furthermore, the weight ratio of coniferous pulp to broadleaf pulp in step S1 is 5-8:2-5, and preferably, the ratio of coniferous pulp to broadleaf pulp is 7:3.
[0026] Furthermore, the PAE wet strength agent in step S2 is a polyamide-epichlorohydrin resin, the wet strength agent has a solid content of 12-13%, a viscosity of 35-70 cp, and a pH of 4-5.
[0027] Furthermore, the defoaming agent in step S2 is one or more of emulsified silicone oil, high carbon alcohol fatty acid ester complex, polyoxyethylene polyoxypropylene pentaerythritol ether, polyoxyethylene polyoxypropanolamine ether, polyoxypropylene glycerol ether or polydimethylsiloxane.
[0028] Furthermore, in step S3, the starch is cationic starch with a concentration of 2-6%, and the alkyl ketene dimer sizing agent is a cationic alkyl ketene dimer sizing agent with a concentration of 1-4%.
[0029] Furthermore, the impregnation of the dry parts in step S5 is performed using an impregnation solution, and the impregnation solution is calculated by weight, and the raw material composition is as follows:
[0030] 30-50 parts of styrene-acrylic latex, 40-60 parts of phenolic resin, 10-20 parts of polyvinyl alcohol, and 3-5 parts of hydroxypropyl methylcellulose.
[0031] Furthermore, the drying in step S5 is a combination of an infrared drying oven and a drying cylinder, the temperature of the infrared drying oven reaches 220-260°C, first instantaneous ultra-high temperature curing for 3-5 seconds, and then the subsequent oven temperature is 90-140°C for 10-25 seconds.
[0032] Furthermore, by weight, the defoaming agent in step S2 is 0.5 to 1 part, the PAE wet strength agent is 3 to 5 parts, the polyacrylamide is 3 to 5 parts, and the aluminum sulfate is 6 to 10 parts.
[0033] Furthermore, the starch in step S3 is 2 to 6 parts and the alkyl ketene dimer sizing agent is 1 to 4 parts by weight.
[0034] Furthermore, the drying agent is fatty acid salt, ketone, ester and the like.
[0035] The application first mixes coniferous wood pulp and hardwood wood pulp in proportion and crushes them to a specified concentration and beating degree. This process ensures the best bonding strength and air permeability between fibers, laying a solid foundation for subsequent processes. Coniferous wood pulp provides excellent tensile strength and toughness, while the fine fibers of hardwood pulp fill the gaps between fibers, providing the best air permeability and further enhancing the overall strength of the paper.
[0036] Next, add defoaming agent, PAE wet strength agent, polyacrylamide and aluminum sulfate and other chemicals into the adding pool. The wet strength agent is used to improve the wet strength of the paper. At the same time, the added wet strength agent can also make the paper less likely to break during the subsequent process and dipping process. The use of defoaming agent can quickly remove the fine bubbles entrained between fibers, eliminate the foam floating on the surface of the pulp, the air that can be dissolved in the pulp, and the large bubbles on the water surface. The influence of bubbles on the process is eliminated, the formation of holes is avoided, and paper breaks are reduced, ensuring the loss of fibers and wet chemicals. The paper has better uniformity and the quality has been greatly improved. Polyacrylamide can improve the dehydration performance of the pulp, increase the retention rate of fine fibers and fillers, and reduce the consumption of raw materials. Aluminum sulfate can significantly improve the water resistance and anti-seepage performance of the paper, increase the retention rate of fine fibers and fillers, and improve the filtration performance of the pulp, thereby improving the uniformity and strength of the paper.
[0037] Subsequently, the paper formed by the fourdrinier paper machine is sprayed with cationic starch and alkyl ketene dimer sizing agent before pressing. This treatment method can improve the retention rate of alkyl ketene dimer more than the traditional pulp addition, thereby enhancing the sizing effect and significantly improving the physical strength of the paper. The present application uses a combination of infrared drying oven and drying cylinder drying. The temperature of the infrared drying oven reaches 220-260°C, and the first instantaneous ultra-high temperature curing is followed by an oven temperature of 90-140°C. By continuously adjusting the drying curve and optimizing these conditions, the adhesive can be fully cured and the overall structural strength of the sandpaper can be improved. After experimental comparison, the paper dried using this scheme has a tensile strength 3-5% higher than that of normal paper, and the tear resistance is increased by more than 5%.
[0038] The dryer impregnation step uses a special impregnation solution, which contains ingredients such as styrene acrylic latex, phenolic resin, polyvinyl alcohol and hydroxypropyl methylcellulose. These substances work together on the surface of the paper to form a strong and elastic protective film, which not only enhances the wear resistance and heat resistance of the paper, but also gives it excellent bonding ability. Cellulose is used as a toughening agent to improve the toughness of the paper, and hydroxypropyl methylcellulose is used as an efficient adhesive to improve the viscosity of the sandpaper, making the sandpaper more durable and stable. In addition, hydroxypropyl methylcellulose can also improve the suspension of sandpaper and prevent the sedimentation and agglomeration of sand particles during the manufacturing process, thereby ensuring the flatness and consistency of the sandpaper surface. The film-forming properties of hydroxypropyl methylcellulose can effectively improve the wear resistance and heat resistance of sandpaper, extend its service life, and have excellent water retention properties, which helps to control the drying speed and hardness of sandpaper.
[0039] The coating formula used in the front coating layer contains styrene acrylic latex, styrene butadiene latex, polyurethane resin and modified alkali lignin. Polyurethane resin is a polymer material with high strength, tear resistance, wear resistance and other characteristics. It can realize self-crosslinking reaction at high temperature to form a thermoplastic elastomer, which has good wear resistance and yellowing resistance. Modified alkali lignin is added to the coating to improve the hydrophilicity and reactivity of the coating surface. Alkali lignin has a low relative molecular mass and high polydispersity. Its main structural units include syringyl, guaiacyl and p-hydroxyphenyl, and it is pyrolyzed at high temperature. After pyrolysis, guaiacyl and methoxycatechol will fully combine with the fiber to improve the anti-slip performance. The back coating layer also contains nano-silicon dioxide, nano-calcium carbonate, glycerol, modified alkali lignin and a drying agent. The nano-calcium carbonate has a particle size of 0.01 micron to 0.1 micron. Compared with ordinary calcium carbonate, its particle size is particularly small and has good compatibility with latex. The particle size of nano-silicon dioxide is 10 to 15 nanometers. It has small particle size, many micropores, large specific surface area and good dispersibility.
[0040] Nanomaterials such as nano calcium carbonate and nano silicon dioxide are added to the coating as anti-skid particles to improve the anti-skid performance of the paper. After these nanomaterials are modified, they are combined with water-based emulsions to form a composite coated anti-skid paper with a high friction coefficient. Through experiments, it was found that when the mass ratio of nano silicon dioxide to nano calcium carbonate is 1:7, nano silicon dioxide is 1 part, nano calcium carbonate is 7 parts, glycerin is 2 parts, and the drying temperature is 70°C, the static friction coefficient of the prepared composite anti-skid paper can reach 0.802, showing excellent anti-skid performance.
[0041] Glycerol is added to the coating as a binder to adjust the viscosity of the coating, which also improves the anti-skid performance to a certain extent. When the mass fraction of nano calcium carbonate is 4%, the static friction coefficient has reached the standard requirement, but the viscosity of the coating is 120mPa·s, which is higher than the suitable viscosity widely used in industrial production, that is, 20-100mPa·s. Glycerol has the effect of reducing the viscosity of the coating. Through experiments, it was found that when the mass fraction of glycerol is 2%, the static friction coefficient of the prepared anti-skid paper is 0.707 and the coating viscosity is 78.50mPa·s. At this time, it has the best friction effect.
[0042] A drying agent is a substance that can accelerate the drying of the coating. Its function is to accelerate the oxidation, polymerization, and drying of the coating to achieve the purpose of quick drying. It can reduce the flow rate of the liquid on the surface of the paper, thereby reducing the leveling. The reduction in leveling will make the coating more concave and convex, and prevent the smooth coating surface after leveling, which reduces the friction of the coating. Water-based drying agents can reduce the surface tension of water, making it easier for the water in the coating to detach from the surface. In this way, the water on the surface of the coating is more easily absorbed and evaporated by the air, thereby promoting the drying process. Secondly, water-based drying agents can increase the evaporation rate of the solvent, thereby taking away the water from the surface of the coating more quickly.
[0043] Finally, the grooved roller replaces the traditional soft pressure roller, which makes the product surface have a unique texture, enhances the friction and aesthetics, and also has a certain anti-counterfeiting function. The main materials of the soft pressure roller are cast iron and stainless steel. If the material is harder, it will damage the coating on the coating surface and reduce the friction effect. The grooved roller is to add patterns on the steel roller, which can make the product surface have a concave and convex feeling, enhance the three-dimensional sense of the product, increase friction, increase aesthetics, and have a certain anti-counterfeiting performance. DETAILED DESCRIPTION
[0044] The technical scheme of the present invention and its effects are further described below by specific examples. The following examples are only used to illustrate the content of the present invention and are not used to limit the protection scope of the present invention. Simple changes made to the present invention by applying the concept of the present invention are all within the scope of the protection claimed by the present invention.
[0045] The equipment used in the preparation method of the present invention can be the well-known equipment in the art. The raw materials used in the present invention are commercially available unless otherwise specified.
[0046] The PAE wet strength agent is polyamide-epichlorohydrin resin, with a solid content of 12-13%, a viscosity of 35-70cp, and a pH of 4-5; the modified alkali lignin is sulfonated modified alkali lignin, produced by Guangzhou Fengsen New Materials Co., Ltd., model MN-1; the alkyl ketene dimer sizing agent is a cationic type, produced by Zhejiang Chuanhua Huayang Chemical Co., Ltd.; the defoaming agent is a high-carbon alcohol fatty acid ester complex produced by Zhejiang Chuanhua Huayang Chemical Co., Ltd., and the drying agent is produced by Shandong Qilin Chemical Co., Ltd., model DOP.
[0047] Example 1
[0048] The present application provides a non-slip paper base for coating molds, which comprises the following structures in order: a front coating layer, a substrate and a back coating layer, wherein the front coating layer and the back coating layer are attached to both sides of the substrate, and the preparation method thereof comprises the following steps:
[0049] S1, crushing coniferous and hardwood pulps at a crushing concentration of 5.0%, with a weight ratio of coniferous pulp to hardwood pulp of 8:5, and beating the pulps with a pulping machine to a beating degree of 40°SR to obtain beaten wood pulp;
[0050] S2, put 1 part of defoamer, 4 parts of PAE wet strength agent, 4 parts of polyacrylamide, and 8 parts of aluminum sulfate into the adding tank, pump the wood pulp obtained in S1 into the adding tank in advance, and adjust the concentration to 3wt%, perform internal sizing, and obtain slurry;
[0051] S3, forming the slurry in step S2 through a fourdrinier paper machine, spraying starch on the wet end after forming, spraying 4 parts of starch and 3 parts of alkyl ketene dimer sizing agent on the front and back of the paper surface at the same time, and performing web-side glue spraying;
[0052] S4, after the web is sprayed with glue, it is pressed and then dried at a temperature of 90°C for 180 seconds;
[0053] S5, adding a sizing machine to carry out cadre dipping, the dipping solution includes 30 parts of styrene-acrylic latex, 60 parts of phenolic resin, 10 parts of polyvinyl alcohol, and 5 parts of hydroxypropyl methylcellulose by weight, and then drying, using an infrared drying oven and a drying cylinder drying method, the infrared drying oven temperature reaches 240 ° C, first instantaneous ultra-high temperature curing for 4 seconds, and then the oven temperature is 100 ° C for 20 seconds;
[0054] S6, after drying, calendering is performed using a calender to obtain a substrate;
[0055] S7, coating the front side of the calendered substrate, wherein the coating comprises 30 parts of styrene acrylic latex, 60 parts of styrene butadiene latex, 10 parts of polyurethane resin, and 7 parts of modified alkali lignin by weight, and then cross-linking is performed at 130° C. for 120 seconds to obtain a front coating layer;
[0056] S8, then back coating is performed, the coating comprises, by weight, 30 parts of styrene-acrylic latex, 60 parts of styrene-butadiene latex, 1 part of nano-silicon dioxide, 7 parts of nano-calcium carbonate, 2 parts of glycerol, 3 parts of modified alkali lignin, and 2 parts of drying agent, and then high-temperature cross-linking is performed at 150° C. for 30 seconds to obtain a back coating layer;
[0057] S9, modifying the paper using a groove roller;
[0058] S10, using a winding device to roll up, and packaging to obtain the anti-slip coated paper base.
[0059] Example 2
[0060] The present application provides a non-slip paper base for coating molds, which comprises the following structures in order: a front coating layer, a substrate and a back coating layer, wherein the front coating layer and the back coating layer are attached to both sides of the substrate, and the preparation method thereof comprises the following steps:
[0061] S1, crushing coniferous and hardwood pulps at a crushing concentration of 4.0%, with a weight ratio of coniferous pulp to hardwood pulp of 5:2, and beating the pulps with a pulping machine to a beating degree of 30°SR to obtain beaten wood pulp;
[0062] S2, 0.5 parts of defoamer, 5 parts of PAE wet strength agent, 3 parts of polyacrylamide, and 6 parts of aluminum sulfate are placed in a adding tank, the beating wood pulp obtained in S1 is pumped into the adding tank in advance, and the concentration is adjusted to 3.5wt%, and internal sizing is performed to obtain slurry;
[0063] S3, forming the slurry in step S2 through a fourdrinier paper machine, spraying starch on the wet end after forming, spraying 2 parts of starch and 1 part of alkyl ketene dimer sizing agent on the front and back of the paper surface at the same time, and performing web-side glue spraying;
[0064] S4, after the web is sprayed with glue, it is pressed and then dried at a temperature of 130°C for 30 seconds;
[0065] S5, add a sizing machine to carry out cadre dipping, the dipping solution includes 50 parts of styrene acrylic latex, 40 parts of phenolic resin, 20 parts of polyvinyl alcohol, and 3 parts of hydroxypropyl methylcellulose by weight, and then dry it, using an infrared drying oven and a drying cylinder drying method, the infrared drying oven temperature reaches 260 ° C, first instantaneous ultra-high temperature curing for 5s, and then the oven temperature is 90 ° C for 25s;
[0066] S6, after drying, calendering is performed using a calender to obtain a substrate;
[0067] S7, coating the front side of the calendered substrate, wherein the coating comprises 60 parts by weight of styrene-acrylic latex, 30 parts by weight of styrene-butadiene latex, 20 parts by weight of polyurethane resin, and 3 parts by weight of modified alkali lignin, and then cross-linking is performed at a high temperature of 150° C. for 30 seconds to obtain a front coating layer;
[0068] S8, then back coating is performed, the coating comprises 60 parts by weight of styrene-acrylic latex, 30 parts by weight of styrene-butadiene latex, 2 parts by weight of nano-silicon dioxide, 2 parts by weight of nano-calcium carbonate, 2 parts by weight of glycerol, 7 parts by weight of modified alkali lignin, and 1 part by weight of a drying agent, and then high-temperature cross-linking is performed at 130° C. for 120 seconds to obtain a back coating layer;
[0069] S9, modifying the paper using a groove roller;
[0070] S10, using a winding device to roll up, and packaging to obtain the anti-slip coated paper base.
[0071] Example 3
[0072] The present application provides a non-slip paper base for coating molds, which comprises the following structures in order: a front coating layer, a substrate and a back coating layer, wherein the front coating layer and the back coating layer are attached to both sides of the substrate, and the preparation method thereof comprises the following steps:
[0073] S1, crushing coniferous and hardwood pulps at a crushing concentration of 3.5%, with a weight ratio of coniferous pulp to hardwood pulp of 7:3, and beating the pulps with a pulping machine to a beating degree of 35°SR to obtain beaten wood pulp;
[0074] S2, 0.5 parts of defoamer, 3 parts of PAE wet strength agent, 5 parts of polyacrylamide, and 10 parts of aluminum sulfate are placed in a adding tank, the beating wood pulp obtained in S1 is pumped into the adding tank in advance, and the concentration is adjusted to 3.5wt%, and internal sizing is performed to obtain slurry;
[0075] S3, forming the slurry in step S2 through a fourdrinier paper machine, spraying starch on the wet end after forming, spraying 6 parts of starch and 4 parts of alkyl ketene dimer sizing agent on the front and back of the paper surface at the same time, and performing web-side glue spraying;
[0076] S4, after the web is sprayed with glue, it is pressed and then dried at a temperature of 110°C for 100s;
[0077] S5, add a sizing machine to carry out cadre dipping, the dipping solution includes 40 parts of styrene acrylic latex, 50 parts of phenolic resin, 15 parts of polyvinyl alcohol, and 4 parts of hydroxypropyl methylcellulose by weight, and then dry it, using an infrared drying oven and a drying cylinder drying method, the infrared drying oven temperature reaches 220 ° C, first instantaneous ultra-high temperature curing for 5s, and then the oven temperature is 140 ° C for 15s;
[0078] S6, after drying, calendering is performed using a calender to obtain a substrate;
[0079] S7, coating the front side of the calendered substrate, wherein the coating comprises 50 parts by weight of styrene acrylic latex, 50 parts by weight of styrene butadiene latex, 15 parts by weight of polyurethane resin, and 5 parts by weight of modified alkali lignin, and then cross-linking is performed at a high temperature of 140° C. for 80 seconds to obtain a front coating layer;
[0080] S8, then back coating is performed, the coating comprises, by weight, 50 parts of styrene-acrylic latex, 50 parts of styrene-butadiene latex, 2 parts of nano-silicon dioxide, 12 parts of nano-calcium carbonate, 1 part of glycerol, 5 parts of modified alkali lignin, and 1 part of drying agent, and then high-temperature cross-linking is performed at 140° C. for 80 seconds to obtain a back coating layer;
[0081] S9, modifying the paper using a groove roller;
[0082] S10, using a winding device to roll up, and packaging to obtain the anti-slip coated paper base.
[0083] The preparation method of Comparative Example 1 is the same as that of Example 1, but no modified alkali lignin is added to the coatings applied on the front and back surfaces.
[0084] The preparation method of Comparative Example 2 is the same as that of Example 1, but in step S5, the drying is performed in an oven instead of an infrared drying oven, and the temperature is set to 100°C.
[0085] The preparation method of Comparative Example 3 is the same as that of Example 1, but double-sided coating is not performed, and only the back coating layer is retained.
[0086] The preparation method of Comparative Example 4 is the same as that of Example 1, but double-sided coating is not performed and only the front coating layer is retained.
[0087] The products obtained from the embodiments and comparative examples were subjected to performance tests:
[0088] (1) Air permeability test:
[0089] By comparing the air permeability, the permeability of paper to air or other gases under different pressures can be evaluated. The GB / T 22901-2008 standard method is used: This method measures the average air flow through a unit area of a sample per unit time under a unit pressure difference, expressed in micrometers per Pascal seconds.
[0090] (2) Roughness test:
[0091] GB / T 2679.4-1994 paper and paperboard roughness determination method, namely air leakage method, is adopted. This method is based on the principle of measuring the air flow between the paper surface and the metal ring surface under a specific pressure. The rougher the paper surface, the greater the air flow and the higher the roughness value.
[0092] (3) Water resistance test:
[0093] The QB / T 1668-1992 absorbency tester method is used. The absorbency tester method is a method for accurately measuring the water absorption of paper and paperboard. The surface water absorption value is calculated by measuring the mass change of paper after absorbing water under specific conditions.
[0094] (4) Leveling test:
[0095] The leveling process of paper coating refers to the process in which the coating slowly flows on the paper surface and gradually forms a smooth surface due to the effect of surface tension after coating. Usually, the paper is tilted 45°, and a drop of water is dropped with a dropper to test the width of the water when it flows on the paper.
[0096] The test results are shown in the table below.
[0097]
Claims
1. A non-slip paper base for coating molds, characterized in that: The invention comprises the following structures in order: a front coating layer, a substrate and a back coating layer, wherein the front coating layer and the back coating layer are attached to both sides of the substrate; The front coating layer comprises the following components by weight: 30-60 parts of styrene-acrylic latex, 30-60 parts of styrene-butadiene latex, 10-20 parts of polyurethane resin, 3-7 parts of modified alkali lignin; The substrate is a paper substrate; The back coating layer comprises the following components by weight: 30-60 parts of styrene-acrylic latex, 30-60 parts of styrene-butadiene latex, 1-2 parts of nano-silicon dioxide, 2-12 parts of nano-calcium carbonate, 1-2 parts of glycerol, 3-7 parts of modified alkali lignin, and 1-2 parts of drying agent.
2. The method for preparing the anti-slip paper base for coating mold according to claim 1, characterized in that: The following steps are involved: S1, crushing coniferous and hardwood pulp according to a crushing mass concentration of 5.0%-4.0%, and beating the pulp with a refiner to a beating degree of 30-40°SR to obtain beaten wood pulp; S2: Pump the wood pulp obtained in S1 into the adding tank in advance, and adjust the mass concentration to 3%-3.5%, put the defoamer, PAE wet strength agent, polyacrylamide and aluminum sulfate into the adding tank, perform internal sizing, and obtain slurry; S3, forming the slurry in step S2 through a fourdrinier paper machine, spraying starch on the wet end after forming, spraying starch and alkyl ketene dimer sizing agent on the front and back of the paper surface at the same time, and performing web-end glue spraying; S4, after the web is sprayed with glue, it is pressed and then dried at a temperature of 90-130°C for 30-180s; S5, add the glue applicator to dip the cadres into glue, and then dry them; S6, after drying, calendering is performed using a calender to obtain a substrate; S7, coating the front side of the calendered substrate, and then crosslinking at 130°C-150°C for 30-120s to obtain a front side coating layer; S8, then back coating is performed, and then high temperature cross-linking is performed at 130° C.-150° C. for 30-120 seconds to obtain a back coating layer; S9, modifying the paper using a groove roller; S10, using a winding device to roll up, and packaging to obtain the anti-slip coated paper base.
3. The method for preparing the anti-slip paper base for coating mold according to claim 2, characterized in that: The weight ratio of coniferous pulp to broadleaf pulp in step S1 is 5-8:2-5.
4. The method for preparing the anti-slip paper base for coating mold according to claim 2, characterized in that: The PAE wet strength agent in step S2 is polyamide-epichlorohydrin resin, with a solid content of 12-13%, a viscosity of 35-70 cp, and a pH of 4-5.
5. The method for preparing the anti-slip paper base for coating mold according to claim 2, characterized in that: The defoaming agent in step S2 is one or more of emulsified silicone oil, high carbon alcohol fatty acid ester complex, polyoxyethylene polyoxypropylene pentaerythritol ether, polyoxyethylene polyoxypropanolamine ether, polyoxypropylene glycerol ether or polydimethylsiloxane.
6. The method for preparing the anti-slip paper base for coating mold according to claim 2, characterized in that: In step S3, the starch is cationic starch with a concentration of 2-6 wt %, and the alkyl ketene dimer sizing agent is a cationic alkyl ketene dimer sizing agent with a concentration of 1-4 wt %.
7. The method for preparing the anti-slip paper base for coating mold according to claim 2, characterized in that: The dry part of step S5 is dipped in a dipping solution, and the dipping solution is calculated by weight, and the raw material composition is as follows: 30-50 parts of styrene-acrylic latex, 40-60 parts of phenolic resin, 10-20 parts of polyvinyl alcohol, and 3-5 parts of hydroxypropyl methylcellulose.
8. The method for preparing the anti-slip paper base for coating mold according to claim 2, characterized in that: The drying in step S5 is a combination of an infrared drying oven and a drying cylinder. The temperature of the infrared drying oven reaches 220-260°C, and the instantaneous ultra-high temperature curing is performed for 3-5 seconds, and then the subsequent oven temperature is 90-140°C for 10-25 seconds.
9. The method for preparing the anti-skid paper base for coating mold according to claim 2, characterized in that: By weight, the defoamer described in step S2 is 0.5-1 parts, the PAE wet strength agent is 3-5 parts, the polyacrylamide is 3-5 parts, and the aluminum sulfate is 6-10 parts.
10. The method for preparing the anti-skid paper base for coating mold according to claim 2, characterized in that: By weight, the starch in step S3 is 2-6 parts, and the alkyl ketene dimer sizing agent is 1-4 parts.
Citation Information
Patent Citations
Biopolymer sizing agents
CN109477308A
Back paint for back anti-skid coating of coated abrasive tool paper and method for preparing coated abrasive tool paper from back paint
CN110791997A
Pre-coating-free kraft paper for coated abrasive tool and preparation method thereof
CN110820422A
Method for improving water vapor barrier property of food packaging paper under high temperature and high humidity
CN112900148A
Abrasive articles and methods for forming the same
WO2023183488A1